Immunopotentiators in Modern Vaccines - Virgil E J C Schijns [ editor ] (Elsevier Academic Press, 2006)
This book provides an in-depth insight and overview of a number of most promising immunopotentiators in modern vaccines. In contrast to existing books on the subject it provides recent data on the critical mechanisms governing the activity of vaccine adjuvants and delivery systems. Knowledge of immunological pathways and scenarios of the cells and molecules involved is described and depicted in comprehensive illustrations. * Contributions from leading international authorities in the field * Well-illustrated, informative figures present the interactions between immunopotentiators and the host immune system * Each chapter lists advantages and potential hurdles for achieving a practical application for the specific immunopentiator.